2009
DOI: 10.1051/0004-6361/200911900
|View full text |Cite
|
Sign up to set email alerts
|

Using binaries containing giants to constrain theories of stellar and tidal evolution

Abstract: Aims. Investigations of stellar and tidal evolution of binary stars with giant components are rare. In this paper, we will investigate such features in three binary systems for which at least one component is a giant star. As some of these giants seem to be in the blue loop, it is an excellent opportunity to investigate the sensitivity of core overshooting on their location in the HR Diagram. We expect that these characteristics shall serve as an incentive to observers to investigate such kinds of binaries, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Observations and predictions have shown that stars with orbital periods P orb 10 days will have circularized while on the main sequence, regardless of spectral type (e.g., Walter 1949;Koch & Hrivnak 1981;Zahn & Bouchet 1989). As stars evolve off of the Contact email: rmroett@umich.edu main sequence and cool while becoming subgiants and giants, circularization is expected for stars with periods P orb 100 days (e.g., Mayor & Mermilliod 1984;Claret 2009). Therefore, RS CVn systems with orbital periods longer than 100 days are likely to retain primordial nonzero eccentricities.…”
Section: Introductionmentioning
confidence: 99%
“…Observations and predictions have shown that stars with orbital periods P orb 10 days will have circularized while on the main sequence, regardless of spectral type (e.g., Walter 1949;Koch & Hrivnak 1981;Zahn & Bouchet 1989). As stars evolve off of the Contact email: rmroett@umich.edu main sequence and cool while becoming subgiants and giants, circularization is expected for stars with periods P orb 100 days (e.g., Mayor & Mermilliod 1984;Claret 2009). Therefore, RS CVn systems with orbital periods longer than 100 days are likely to retain primordial nonzero eccentricities.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed value That denotes binaries formed of a late-type giant and a hot dwarf, and are characterised by a composite spectrum, showing the superimposed features of both components. These systems, and especially the eclipsing pairs (EB-SB2), are excellent benchmarks of stellar evolutionary models (e.g Claret 2009.…”
mentioning
confidence: 99%